THE DETERMINANTS OF MANAGEMENT FORECASTS ERROR AND THE IPO UNDERPRICING: A CASE STUDY OF INDONESIAN IPO - Yanthi Hutagaol; Florens Siauw; Irwan A. Ekaputra (Journal of Applied Finance & Accounting, 2011)
To reduce the well-known information asymmetry in the IPO market, the issuing firms are required to publish offering prospectuses. One type of information disclosed in the prospectus is the management financial forecasts in which the IPO firms predict expected earnings at the end of year after the listing. The purpose of this study is to investigate the determinants of forecasted error published by the management in the IPO prospectuses. This study observes six possible determinants that affect the absolute forecast errors (AFE). Furthermore, this study also examines whether the earning forecast errors could explain the IPO stylish underpricing phenomenon.A sample of 124 IPO firms that went public in Indonesian Stock Exchange (prior Jakarta Stock Exchange) during the 1997 – 2005 period. The results show that the research models proposed are valid models. The management AFE is determined by firm size, forecast interval period, industry, and the firm business range.  This study also finds that the AFE is positively related to the IPO underpricing, suggesting that the higher the forecast errors, the more underpriced is the IPO. Moreover, it is also found that market condition also influences the underpricing level in Indonesian IPO market.